A Part of, or Apart from, Me?: Linking Dynamic Founder-Venture Identity Relationships to New Venture Strategy - Crosina, Eliana; Pratt, Michael G.; Lifshitz, Hila (Organization Science, 2024)
Based on a three-year inductive field study of first-time founders, we reveal the dynamic identity relationships that tie founders to their ventures: what such relationships comprise, how they evolve over time, and with what strategic implications for the development of new businesses. Specifically, we found that such relationships comprise both identification and construals, which capture the degree to which founders saw their ventures as self-defining and founder-venture psychological distance. Construals, and shifts in construals over time, were critical in explaining how entrepreneurs handled venture-related challenges, as well as how they strategically (re)focused their ventures in terms of scope, whether by diversifying or specializing. By explaining these dynamics, we contribute to research on entrepreneurial identity as well as to construal level theory. In addition, as we distinguish construals from identification, we highlight the importance of construals for understanding identity relationships beyond entrepreneurship. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2021.15271 .